PERANCANGAN PROTOTIPE ROBOT PENGHALANG GARIS BERBASIS ROBO TX CONTROLLER - Subiyantoro Subiyantoro; Nurwijayanti KN (JURNAL TEKNOLOGI INDUSTRI, 2012)
Robot barrier line designed and developed as a platform for the development of robots in the future. Robot control system was designed based on Robo TX Controller and is designed to be able to move forward, backward, and turn in place or the desiredlocation. In the design o f the prototype robot is necessary a barrier line controller ( ROBO TX Controller ) and infrared trail sensor, where the sensor can distinguish between black and white. If the robot track a black line then the robot will stop and make a turn to continue it is work. Obtained in the testing and analysis that the robot is able to do it is job as it should be . Data tables from the test range for robot obtained error of 0.80 % to 0.86 % in the black line sensor readings. Key words : Robo TX, Sensor, Prototype, Autonomous